2018
DOI: 10.1186/s12917-018-1371-x
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory investigation into the role of largemouth bass virus (Ranavirus, Iridoviridae) in smallmouth bass mortality events in Pennsylvania rivers

Abstract: BackgroundMortality episodes have affected young-of-year smallmouth bass (Micropterus dolomieu) in several river systems in Pennsylvania since 2005. A series of laboratory experiments were performed to determine the potential role of largemouth bass virus (Ranavirus, Iridoviridae) in causing these events.ResultsJuvenile smallmouth bass experimentally infected with the largemouth bass virus exhibited internal and external clinical signs and mortality consistent with those observed during die-offs. Microscopical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
29
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 20 publications
2
29
1
1
Order By: Relevance
“…In the same way, severe bacteria and virus co‐infections were reported during CyHV‐2 infections and synergistically lead to the death of fish (Adamek, Hellmann, Jung‐Schroers, Teitge, & Steinhagen, ; Fichi et al., ; Sahoo et al., ). In smallmouth bass, co‐infection of largemouth bass virus (LMBV) and Flavobacterium columnare lead to a temperature‐dependent increase in mortality (Boonthai et al., ). Another study indicated a tendency for co‐infections of infectious haematopoietic necrosis virus (IHNV) with another member flavobacteria, Flavobacterium psychrophilum, in sockeye salmon (Chappell, Epp, & Zwollo, ).…”
Section: Introductionmentioning
confidence: 99%
“…In the same way, severe bacteria and virus co‐infections were reported during CyHV‐2 infections and synergistically lead to the death of fish (Adamek, Hellmann, Jung‐Schroers, Teitge, & Steinhagen, ; Fichi et al., ; Sahoo et al., ). In smallmouth bass, co‐infection of largemouth bass virus (LMBV) and Flavobacterium columnare lead to a temperature‐dependent increase in mortality (Boonthai et al., ). Another study indicated a tendency for co‐infections of infectious haematopoietic necrosis virus (IHNV) with another member flavobacteria, Flavobacterium psychrophilum, in sockeye salmon (Chappell, Epp, & Zwollo, ).…”
Section: Introductionmentioning
confidence: 99%
“…One potential emerging pathogen is Largemouth Bass virus, which was isolated from age-0 after the onset of disease events (Smith et al 2015 ) and its occurrence is consistent with the dispersal of Largemouth Bass virus in the eastern USA (Grizzle and Brunner 2003 ). Recent work by Boonthai et al (2018) found that Largemouth Bass virus can cause mortality in age-0 Smallmouth Bass alone or in combination with other pathogens in a laboratory setting. Similarly, M. inornatus had not been previously reported from the Susquehanna basin prior to investigating the initial young-of-the-year mortalities in 2005 (Walsh et al 2012).…”
Section: Results and Discussion Temporal Changes In Catch Rates Mortmentioning
confidence: 92%
“…One possible explanation is that nutrient and sediment inputs from agricultural activities may be altering instream habitat and subsequently increasing the availability of suitable habitat conditions for invertebrate host populations (e.g., aquatic oligochaetes; Kaeser and Sharpe 2006 ). Environmental conditions, including elevated temperatures, like those commonly observed in the Susquehanna River can also affect infectivity and mortality of age-0 Smallmouth Bass associated with pathogens such as Largemouth Bass virus and F. columnare (Boonthai et al 2018 ), suggesting that as water conditions warm as a result of climate change, susceptibility of Smallmouth Bass populations at higher latitudes becomes more likely. Boonthai et al ( 2018 ) also found that Largemouth Bass virus strains isolated from Susquehanna drainage sites were more virulent in laboratory studies than isolates from other drainages to age-0 Smallmouth Bass.…”
Section: Results and Discussion Temporal Changes In Catch Rates Mortmentioning
confidence: 99%
“…The discovery of M. Inornatus in Susquehanna River YOY smallmouth bass was one of many stressors identified as potential risk factors for YOY disease and mortality (Smith, Blazer, Walsh, Iwanowicz, & Sperry, ; Walsh et al., ). Multiple pathogens and parasites have been identified including bacteria (e.g., multiple aeromonads, Flavobacterium columnare (Bernardet and Grimont); Starliper, Blazer, Iwanowicz, & Walsh, ), largemouth bass virus (Boonthai et al., ; Smith et al., ; Starliper et al., ), trematodes (Smith et al., ) and cestodes (Walsh et al., ). In addition to pathogens and parasites, water quality concerns including elevated water temperatures, suboptimal dissolved oxygen concentrations and contaminants have also been investigated in regard to the overall health of YOY smallmouth bass in the Susquehanna River Basin (Blazer et al., ; Chaplin, Crawford, & Brightbill, ; Smith et al., ; Walsh et al., ).…”
Section: Introductionmentioning
confidence: 99%